A STUDY ON THE PROXIMATE ANALYSIS OF HYDROGENATED FAT IN BAKERY PRODUCTS - MANIVEL K; JOHN R WILLIAMS; MOYEENUDIN HM (Innovare Journal of Food Sciences, 2019)
Margarine is an important functional ingredient for several bakery and confectionary products. It places a major role in the organoleptic attributes of these bakery products. This article contextualizes on “Bakery Products” available in Indian market. It is analyzed and tested through laboratory using various methods of test such as phytochemical screening, proximate analysis, and elemental analysis which are the major laboratory test done. In that subcategory test such as flavonoids, tannis, alkaloids, polyphenols etc. In that, each product is sampled, analyzed, and tested by chemical to know the exact quantity and the quality of various ingredients of the product and to know how much it is important for that packet products manufacturer.